The Effects of Oxide Layer on Co-Cr-Mo: Preliminary Study In-vitro - Mas Ayu, Hassan; S., Izman; Mohammed Rafiq, Abdul Kadir; R., Daud; Salwani, Mohd Salleh; Mohd Faiz, Mohd Yusoff; Mahmood, Anwar; G., Krishnamurithy; T., Tamarul (2015)
The effects of oxide interlayer on cobalt-chromium-molybdenum substrate were investigated in order to improve the adhesion strength of HA coating and cell responses. Substrates were oxidized at temperature range of 850°C to 1250°C. Oxidized substrates were then coated with HA slurry using dip coating technique. Analysis of surface morphology, thickness and chemical composition of oxide interlayer prior to HA coating were performed using field-emission scanning electron microscopy, energy dispersive X-ray spectroscopy and grazing X-ray diffraction respectively. It seems that rough surface of oxide interlayer provides better mechanical interlocking of HA particles to the substrate surface. In addition, the HA coated substrates with oxide interlayer also demonstrate strong attachment and proliferation of cells compared to HA coated substrates without oxide interlayer. It is concluded that the introduction of an intermediate oxide layer on Co-Cr-Mo substrate prior to HA coating has shown a positive effect in terms of increment of the adhesion strength of HA coating as well as cell bioactivity performance.